The Mortal Instruments: City of Bones - Book 1 - Clare, Cassandra (New York : M.K. McElderry Books, 2007)
Suddenly able to see demons and the Shadowhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizarre world when her mother disappears and Clary herself is almost killed by a monster.
Ages 14 up.
Accelerated Reader AR